How tribology has been helping us to advance and to survive - Stachowiak, Gwidon (2017)
Movement between contacting surfaces ranges from macro to micro scales, from the movement of continental plates and glaciers to the locomotion of animals and insects. Surface topographies, lubricant layers, contaminants, operating conditions, and others control it, i.e., this movement depends on the tribological characteristics of a system. Before the industrial revolution, friction and wear were controlled by the application of animal fat or oil. During the industrial revolution, with the introduction of trains and other machinery, the operating conditions at the contacting surfaces changed dramatically. New bearings were designed and built and simple lubrication measures were no longer satisfactory. It became critical to understand the lubrication mechanisms involved. During that period, solid theoretical foundations, leading to the development of new technologies, were laid. The field of tribology had gained a significant prominence, i.e., it became clear that without advancements in tribology the technological progress would be limited. It was no longer necessary to build oversized ship bearings hoping that they would work. The ship or automobile bearings could now be optimized and their behavior predicted. By the middle of the 20th century, lubrication mechanisms in non-conformal contacts, i.e., in gears, rolling contact bearings, cams and tappets, etc., were also finally understood. Today, we face new challenges such as sustainability, climate change and gradual degradation of the environment. Problems of providing enough food, clean water and sufficient energy to the human population to pursue a civilized life still remain largely unsolved. These challenges require new solutions and innovative approaches. As the humanity progresses, tribology continue to make vital contributions in addressing the demands for advanced technological developments, resulting in, for example, reducing the fuel consumption and greenhouse gases emission, increasing machine durability and improving the quality of life through artificial implants, among the others.